1994
DOI: 10.1002/hlca.19940770131
|View full text |Cite
|
Sign up to set email alerts
|

NMR of Terminal Oxygen. Part 14. Kinetically stabilized simple enols containing methylated uracil groups: Application of a 17O‐NMR test of H‐bonding

Abstract: In the crystalline N,N'-dimethylated uracil derivatives Za, b, the kinetically stabilized enol group forms an H-bond with 0-C(4), as demonstrated by increased shielding of specifically labelled 2a and 2b in the I70-NMR spectra (~lS('~o)(C(4)-0) = -30 ppm); absence of dilution and solvent effects show that the H-bridge is intramolecular, forming an eight-membered chelate ring. The (apparent) shielding effect dS("O) in Za,h is larger than that in salicylamide. The strong H-bond explains why the enols 2, in spite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) spectroscopy of 1 H, 13 C, and 15 N nuclei has become an indispensable technique for studying nucleic acid structures. , Despite the fact that oxygen is also an abundant element in nucleic acid molecules, only scattered studies can be found in the literature that employ 17 O ( I = 5 / 2 ) NMR to investigate molecules related to nucleic acids. The lack of experimental 17 O NMR data is a direct consequence of the fact that it is intrinsically difficult to obtain high-resolution NMR spectra for quadrupolar nuclei. For 17 O NMR, two major factors contribute to the practical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy of 1 H, 13 C, and 15 N nuclei has become an indispensable technique for studying nucleic acid structures. , Despite the fact that oxygen is also an abundant element in nucleic acid molecules, only scattered studies can be found in the literature that employ 17 O ( I = 5 / 2 ) NMR to investigate molecules related to nucleic acids. The lack of experimental 17 O NMR data is a direct consequence of the fact that it is intrinsically difficult to obtain high-resolution NMR spectra for quadrupolar nuclei. For 17 O NMR, two major factors contribute to the practical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Zhuo et al . reported the synthesis of 1,3‐dimethyl‐[4‐ 17 O]‐uracil and 1,3,6‐trimethyl‐[4‐ 17 O]‐uracil from unlabeled uracils.…”
Section: Synthetic Challengesmentioning
confidence: 99%
“…We previously observed eight-membered-rings formed by intramolecular Hbonding between the side chain enolic OH and the uracil C(4)O in 1,3-dimethyl-5-(3-cyano-3-hydroxypropan-3-en-1-yl)uracil [10]. Gellman and co-workers [11] have reported intramolecularly H-bonded eight-membered rings for diamides.…”
mentioning
confidence: 99%